Scurvy presenting with limp and weakness: a case report - Robin M. Lund; Mara L. Becker; Steven Shapiro; Tyler Allison; Julia G. Harris (BMC, 2019)
Abstract Background Scurvy is one of the oldest diseases known to mankind. Although presently rare in the developed world, scurvy was a common potentially fatal disease. In recent times, the most common risk factors for scurvy include alcoholism, low socioeconomic status, and severely poor nutrition or dietary restriction secondary to psychiatric illness or developmental disorders. Our case demonstrates the importance of having a high index of clinical suspicion of an uncommon disease in developed countries and emphasizes the necessity of a dietary screening that could potentially reduce extensive work-up in patients with nonspecific complaints. Case presentation We report a case of a 3-year-old previously healthy female originally seen in the rheumatology clinic for limp. She developed weakness and was admitted to the hospital for further evaluation. She underwent extensive diagnostic testing including blood work, magnetic resonance imaging, lumbar puncture, electromyogram, and nerve conduction studies. Ultimately, her vitamin C level returned undetectable. She had immediate and complete improvement upon starting vitamin C supplementation. Conclusions Despite being developmentally appropriate, our patient's refusal to eat fruits or vegetables had limited her diet, emphasizing the importance of obtaining a diet history in a child presenting with an unknown diagnosis. In addition, our patient had no other characteristic features of scurvy, which further supports the need to consider this diagnosis in a child presenting with lower extremity weakness or abnormal gait.